2023
DOI: 10.1017/s1463423623000567
|View full text |Cite
|
Sign up to set email alerts
|

Speaking the same language – a scoping review to identify the terminology associated with social prescribing

Simon Newstead,
Megan Elliott,
Dawn Cavanagh
et al.

Abstract: Aim: To identify the social prescribing-related terminology within the peer-reviewed literature of the UK and the grey literature from Wales. Background: Social prescribing has seen a period of development that has been accompanied by a proliferation of related terminology and a lack of standardisation in the manner in which it is employed. This creates barriers to engagement and impairs communication, both between professionals and members of the public. The Wales School for Social Pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Since SP’s goal is to favor well-being without focusing on a specific health outcome, the time scale for evaluation might also be much longer than usual [ 14 ]. Eventually, a scoping review conducted in Wales revealed a lack of consensus on the terminology used in social prescription practice, leading to miscommunication among professionals, public health decision makers, and the public [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since SP’s goal is to favor well-being without focusing on a specific health outcome, the time scale for evaluation might also be much longer than usual [ 14 ]. Eventually, a scoping review conducted in Wales revealed a lack of consensus on the terminology used in social prescription practice, leading to miscommunication among professionals, public health decision makers, and the public [ 15 ].…”
Section: Introductionmentioning
confidence: 99%